FEATURES OF PREPARING NURSING STUDENTS FOR SPECIALTY EXAMS Ismailova Umida Djuramuradovna - Ismailova Umida Djuramuradovna (Research Focus International Scientific Journal, 2026)
Preparation of nursing students for specialty examinations represents a critical stage in professional formation and certification within contemporary healthcare systems. Specialty exams evaluate not only theoretical knowledge but also clinical reasoning, ethical competence, practical skills, and psychological readiness. This paper analyzes the pedagogical, psychological, and organizational features of preparing nursing students for specialty examinations in the context of competency-based medical education. Drawing upon recent research in nursing education, assessment theory, and professional standards (2010–2025), the study identifies core preparation components: integration of theoretical knowledge with clinical simulation, structured skills training, formative assessment, reflective practice, and stress-management strategies. Particular attention is paid to the alignment between curriculum outcomes and exam standards, the role of objective structured clinical examinations (OSCE), and digital learning technologies. The findings suggest that systematic, competency-oriented preparation enhances exam performance, professional identity formation, and readiness for independent clinical practice. The article proposes a multidimensional preparation model that integrates cognitive, practical, ethical, and emotional domains, contributing to improved quality of nursing education and patient care outcomes.